Spatial Analysis of Macro Economic in Central Java (PDRB Analysis in Year 1993-2003) - Eddy Kiswanto (Universitas Muhammadiyah Surakarta, 2005)
This paper aims to study the spatial analysis macroeconomics condition in central Java from 1993-2001 base on PDRB analysis. Central Java stands in the last position in the economic in Central Java based on PDRB variable and economic growth is in the lowest category in the comparation with another provinces in Java. This is reason why Central Java is categorized as